The principle of reciprocity in the 21st century - David R. DeRemer (Hungarian Academy of Sciences, Institute of Economics, 2016)
The principle of reciprocity is central to trade cooperation. Economic theory characterizes reciprocal policy changes that guide nations from noncooperative policies to the Pareto efficiency frontier. This paper extends the theory of reciprocity to a wide range of settings relevant for 21st century trade negotiations. Global value chains and rigid institutional constraints can lead to nations lacking the policy space necessary to influence relevant local prices abroad. Trade agreements then have a role in addressing these local price externalities in addition to the usual terms-of-trade externality. Yet we show that the standard concept of reciprocity - policy changes that equally increase net export value at world prices - can nonetheless guide nations toward the efficiency frontier. The crucial condition for reciprocity's application is that the policy changes which undo the terms-of-trade inefficiencies also undo the other inefficiencies. We find a set of policies such that no nation can gain from any reciprocal unwinding of trade commitments, and we show that these policies are globally efficient. Such stable policies are then a suitable prediction for trade negotiation outcomes when local price externalities matter. We derive the new predicted outcome and explore its relevance for existing theory and empirics of trade cooperation, including settings with imperfect competition, political economy, and global value chains.
Keywords: F12; F13; F15; L24; 330; trade agreements; principle of reciprocity; GATT/WTO; global value chains